A study of the production system of Cherard Cosmetic Laboratory - Alberto, Raymund; Garcia, Paolo G.; Tan, John Vincent U. (Diliman, Quezon City College of Engineering, 2002)
This study considers the production system of Cheread Cosmetics Laboratory with respect to a Productions/Operations Management standpoint. Cherard Cosmetics Laboratory is a manufacturing firm that produces household care products such as papaya soaps, glycerin soaps, shampoos, and liquid hand soaps. The study aims to be able to apply the tools and techniques of Productions/Operations Management on the company and in doing so, be able to evaluate the production system of the company and to propose and implement improvements on the said system. This was done by gathering the qualitative and quantitative data through direct observation, historical records, and interviews of the company?s management. The group documented the company?s system starting with the company?s mission/vision statement, profile, organizational structure, and systems and procedures. The documentation then centered on the production system of the company based on its operation strategy and competitiveness, SWOT (Strengths, Weaknesses, Opportunities, and Threats) features, core competencies and capabilities, production systems framework, process flow, strategic capacity planning, workforce management, facility location and layout, supply chain, and Just-in-Time management. The group then analyzed the system and identified the problems that were present using a streamline analysis diagram to isolate the main causal problems of the system. These were the inefficiency of the layout, performing with low utilization rates, and uneven production workloads. The group then proposed alternatives that may be implemented to better the production system of the company. Also included are implementation strategies in employing the proposed alternatives and areas of the company?s system that may be further studied under different aspects.
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Cherard Cosmetic Laboratory; Cosmetics industry; Production engineering